The Impact of Green Strategic Management Accounting in Rationalizing Green Decisions for Economic Units Evidence from Iraq - Kadhim, Ezzaddin Hasan; Ali, Ali Razzaq (Journal of Environmental Accounting and Management, 2026)
The aim of this work is to look into the connection between company Green policy, and unpredictability in the environment, as well as the function of green management accounting (GMA). We surveyed data from 77 different Iraqi firms listed on the exchange. GMA use has been positively influenced by the usage of organizational instruments such as company Green issues, top executive engagement, and Green uncertainty. This means that GMA appears to be a valuable and important tool in Iraqi companies to provide data that helps firms better manage their Green performance, and that these findings may be relevant to companies around the world, as they develop capabilities in dealing with perceived Green uncertainty to use GMA tools.